Big Grain3, encoding a purine permease, regulates grain size via modulating cytokinin transport in rice. Issue 5 (29th December 2018) - Xiao, Yunhua; Liu, Dapu; Zhang, Guoxia; Gao, Shaopei; Liu, Linchuan; Xu, Fan; Che, Ronghui; Wang, Yiqin; Tong, Hongning; Chu, Chengcai
Abstract: Grain size is an important agronomic trait affecting grain yield, but the underlying molecular mechanisms remain to be elucidated. Here, we isolated a dominant mutant, big grain3 ( bg3‐D ), which exhibits a remarkable increase of grain size caused by activation of the PURINE PERMEASE gene, OsPUP4 . BG3 / OsPUP4 is predominantly expressed in vascular tissues and is specifically suppressed by exogenous cytokinin application. Hormone profiling revealed that the distribution of different cytokinin forms, in roots and shoots of the bg3‐D mutant, is altered. Quantitative reverse transcription‐PCR (qRT‐PCR) analysis indicated that expression of rice cytokinin type‐A RESPONSE REGULATOR ( OsRR ) genes is enhanced in the roots of the bg3‐D mutant. These results suggest that OsPUP4 might contribute to the long‐distance transport of cytokinin, by reinforcing cytokinin loading into vascular bundle cells. Furthermore, plants overexpressing OsPUP7, the closest homolog of OsPUP4, also exhibited a similar phenotype to the bg3‐D mutant. Interestingly, subcellular localization demonstrated that OsPUP4 was localized on the plasma membrane, whereas OsPUP7 was localized to the endoplasmic reticulum. Based on these findings, we propose that OsPUP4 and OsPUP7 function in a linear pathway to direct cytokinin cell‐to‐cell transport, affecting both its long‐distance movement and local allocation. Abstract : This study cloned a new grain size controlling gene, named Big Grain3, which encodes a cytokinin transporter that localized on cell membrane, thus for the first time revealed that strengthened cytokinin transport can greatly enhance grain size, which could be utilized as a novel strategy for yield improvement.